Mass transport properties of the rabbit aortic wall. - Emma L Bailey; Eleni Bazigou; Piotr S J Sowinski; Peter D Weinberg (PLoS ONE)
Uptake of circulating macromolecules by the arterial wall may be a critical step in atherogenesis. Here we investigate the age-related changes in patterns of uptake that occur in the rabbit. In immature aortas, uptake was elevated in a triangle downstream of branch ostia, a region prone to disease in immature rabbits and children. By 16-22 months, uptake was high lateral to ostia, as is lesion prevalence in mature rabbits and young adults. In older rabbits there was a more upstream pattern, similar to the disease distribution in older people. These variations were predominantly caused by the branches themselves, rather than reflecting larger patterns within which the branches happened to be situated (as may occur with patterns of haemodynamic wall shear stress). The narrow streaks of high uptake reported in some previous studies were shown to be post mortem artefacts. Finally, heparin (which interferes with the NO pathway) had no effect on the difference in uptake between regions upstream and downstream of branches in immature rabbits but reversed the difference in older rabbits, as does inhibiting NO synthesis directly. Nevertheless, examination of uptake all around the branch showed that changes occurred at both ages and that they were quite subtle, potentially explaining why inhibiting NO has only minor effects on lesion patterns in mature rabbits and contradicting the earlier conclusion that mechanotransduction pathways change with age. We suggest that recently-established changes in the patterns of haemodynamic forces themselves are more likely to account for the age-dependence of uptake patterns.